Luisia brachyota (Orchidaceae; Epidendroideae) a new species from China: evidence based on morphological and molecular data - Fu, Hou-Hua; Zhou, Cheng-Yuan; Ma, Liang; Lan, Siren; Chen, Shi-Pin (Phytotaxa, 2023)
We have described and illustrated a new species, Luisia brachyota (Epidendroideae, Orchidaceae), from south Yunnan, China. Morphological comparisons indicated the new species is similar to L. filiformis and L. cordata, but differs from L. brachyota inflorescences 3-or 5-flowered, lip shorter than petals, hypochile thickly fleshy, epichile cordate adaxially with 7 or 9 papillate longitudinal ridges. Molecular analysis based on the nuclear ribosomal ITS and plastid sequences (matK, rbcL, and trnL-trnF) shows that it is a new species.